Genes copy number variation in colorectal cancer patients as a marker of the disease clinical outcome and response to therapy - A. A. Maslov; L. Kh. Chalkhakhyan; S. A. Malinin; G. V. Kaminsky; E. A. Mirzoyan (Южно-Российский онкологический журнал)
Abnormal gene copies, a special type of genetic polymorphism, is a hallmark of most solid tumors, including colorectal cancer. Abnormal copy number of genes leads to tumor-specific genomic imbalance, which manifests itself already in precancerous precursor lesions. The aim of this review was to systematize the scattered data on changes in gene copy number observed in colorectal cancer and their impact on the outcome of the disease and response to therapy. The data from 58 studies was analyzed on gene copy number changes and their expression in primary carcinomas, cell lines and experimental models. This review examines the spectrum of genetic changes that lead to colorectal cancer, describes the most frequent changes in the number of gene copies at different stages of the disease, and changes in the number of gene copies that can potentially affect the outcome of the disease of individual patients or their response to therapy. In fact, aberrant gene copy number as a form of chromosomal imbalance affects a number of genes that provide a metabolic selective advantage for a tumor cell. Changes in the genes copy number in colorectal cancer patients not only positively correlate with changes in their expression, but also affect the levels of gene transcription at the genome-wide scale. Aberrant gene copy numbers are closely related to disease outcome and response to treatment with 5 fluorouracil, irinotecan, cetuximab and bevacizumab. Nevertheless, the possibility of translating the genes copy number index into clinical practice requires further research.